KETERAMPILAN MENULIS TEKS EKSPOSISI BERBANTUAN MEDIA VISUAL DI SMA KARTIKA XIX-4 CIMAHI - een nuraeni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by the problem in writing learning activities, especially in exposition text writing activities that occur in SMA Kartika XIX-4 Cimahi. This study aims to determine the extent of students' ability to write exposition texts. This research uses a descriptive method with a qualitative approach. The sample in this study were all students of class X MIPA with a total of 22 students. The results of this study indicate that all students of class X MIPA can write exposition texts well, although there are some students who have not been able to put their ideas or ideas into written form. Based on the data that has been analyzed, students' written test scores get an average score of 76.68 and fall into the "Good" category. Therefore the results of the average value can be concluded that the skills of writing exposition text aided by visual media are suitable for use in learning activities to write textual exposition.